At the Movies: Risk Sharing and the Economics of Exhibition Contracts - Darren Filson; Fernando Fabre; Alfredo Nava; Paola Rodriguez (Claremont McKenna College, Department of Economics, 2001)
The current literature on sharing contracts emphasizes the importance of asymmetric information and typically assumes that one party is risk neutral while the other is risk averse. This paper describes a real-world contract that is widely used - the movie exhibition contract - and argues that asymmetric information is not the main feature of the environment that leads to sharing. The explanation that fits the facts better is simply that distributors and exhibitors are both risk averse. The analysis suggests that two-sided risk aversion is important in determining contracts.
Keywords: L14; L22; L82; 330; principal agent; licensing; entertainment; film; rental